Post-ion beam induced degradation of copper layers in transmission electron microscopy specimens. (15th October 2015) - Seidel, F; Richard, O; Bender, H; Vandervorst, W
Abstract: Copper containing transmission electron microscopy (TEM) specimens frequently show corrosion after focused ion beam (FIB) preparation. This paper reveals that the corrosion product is a Cu–S phase growing over the specimen surface. The layer is identified by energy-dispersive x-ray spectroscopy, and lattice spacing indexing of power spectra patterns. The corrosion process is further studied by TEM on cone-shaped specimens, which are intentionally stored after FIB preparation with S flakes for short time. Furthermore, a protective method against corrosion is developed by varying the time in the FIB vacuum and the duration of a subsequent plasma cleaning.